Fictional text and chronicles of the life of Abkhazian Muhajirs from Batumi to Adapazari (Anzor Kudba’s story “The Road”) - Chokharadze, Malkhaz ("Intercultural Dialogues" Transactions, 2025)
Anzor Kudba is a descendant of the Abkhazian emigrants who settled in Adjara in the mid-19th century. The writer’s novels and stories reflect the problems of previous eras and modern Georgia, as well as the difficult spiritual world of a person faced with these problems. The story “The Road” was published in the collection “The Symphony of the Great Rain” published in 2015; this story concerns the lives of the descendants of the Abkhazian emigrants, including the Abkhazians of Batumi. The narrative of the story is based on fragments of oral histories. The artistic interpretation of reality is presented with light emotion, without excessive detailing. It is as if the author is trying to portray to the reader images of the past as they have survived in real life in the memory of generations. Accordingly, the volume and function of artistic fiction are minimized. In “The Road”, the author himself tells the story of the Abkhazians of Batumi, and specifically the Kudbas. In this case, the setting, time, and, mainly, the story itself are real. The narrator tells us about his ancestors and his life. More precisely, he introduces us to individual fragments of this life. The time and space of the fragments are not uniform, but nevertheless, we can talk about an orderly composition and a logical sequence of expression of what is said. The story of the Kudba’s emigration begins in the 1960s with three brothers. Two of them settled in the village of Peria in Adjara, and one turned his head towards Turkey and settled in the village of Karadere in the Adapazari province. The descendants of the brothers who remained in Batumi and fled to the Ottoman Empire found each other only at the end of the 20th century, retold their story, and restored their relationship. The emotional background of the story is also created by chronicles of contemporary relations between Georgians and Abkhazians. The writer tries to objectively weigh the movement of the souls of the participants in the tragedy, to pour the truth into artistic faces. The echo of the mentioned thematic arcs is also visible in , The Road”. Obviously, this greatest pain of our era is not alien to the Abkhazians in Turkey.